Cysteine-specific 89Zr-labeled anti-CD25 IgG allows immuno-PET imaging of interleukin-2 receptor-α on T cell lymphomas - Lee, Jin Hee; Jung, Kyung-Ho; Kim, Mina; Lee, Kyung-Han (Frontiers in Immunology, 2022)
Introduction Positron emission tomography (PET) using radiolabeled Abs as imaging tracer is called immuno-PET. Immuno-PET can verify therapeutic Ab delivery and can noninvasively quantify global levels of target expression in tumors of living subjects. The interleukin-2 receptor α chain (IL-2Rα; CD25) is a promising target for immune therapy and radioimmunotherapy of lymphomas. Immuno-PET could facilitate this approach by visualizing CD25 expression in vivo. Methods We prepared 89Zr-anti-CD25 IgG specifically labeled to sulfhydryl moieties by maleimide-deferoxamine conjugation. Results and Discussion CD25(+) SUDHL1 human T-cell lymphoma cells showed high anti-human 89Zr-CD25 IgG binding that reached 32-fold of that of CD25(-) human lymphoma cells and was completely blocked by excess unlabeled Ab. In SUDHL1 tumor-bearing nude mice, pharmacokinetic studies demonstrated exponential reductions of whole blood and plasma activity following intravenous 89Zr-anti-CD25 IgG injection, with half-lives of 26.0 and 23.3 h, respectively. SUDHL1 tumor uptake of 89Zr-CD25 IgG was lower per weight in larger tumors, but blood activity did not correlate with tumor size or blood level of human CD25, indicating minimal influence by circulating soluble CD25 protein secreted from the lymphoma cells. 89Zr-CD25 IgG PET allowed high-contrast SUDHL1 lymphoma visualization at five days. Biodistribution studies confirmed high tumor 89Zr-CD25 IgG uptake (8.7 ± 0.9%ID/g) that was greater than blood (5.2 ± 1.6%ID/g) and organ uptakes (0.7 to 3.5%ID/g). Tumor CD25-specific targeting was confirmed by suppression of tumor uptake to 4.3 ± 0.2%ID by excess unlabeled CD25 IgG, as well as by low tumor uptake of 89Zr-labeled IgG2a isotype control Ab (3.6 ± 0.9%ID). Unlike CD25(+) lymphocytes from mouse thymus that showed specific uptake of anti-mouse 89Zr-CD25 IgG, EL4 mouse lymphoma cells had low CD25 expression and showed low uptake. In immunocompetent mice bearing EL4 tumors, anti-mouse 89Zr-CD25 IgG displayed low uptakes in normal organs as well as in the tumor. Furthermore, the biodistribution was not influenced by Ab blocking, indicating that specific uptake in nontumor tissues was minimal. 89Zr-CD25 IgG immuno-PET may thus be useful for imaging of T-cell lymphomas and noninvasive assessment of CD25 expression on target cells in vivo.